A Dynamic Model of Drag Force for Catalytic Micromotors Based on Navier–Stokes Equations - Wang, Zhen (Micromachines (Basel), 2018)
In past decades, considerable advances have been achieved in micro and nanomotors. Particular attention has been given to self-propelled catalytic micromotors, which have been widely used in cell separation, drug delivery, microsurgery, lithography and environmental remediation. Fast moving, long life micromotors appear regularly, however it seems there are no solutions yet that thoroughly clarify the hydrodynamic behavior of catalytic micromotors moving in fluid. Dynamic behavior of this kind of micromotors is mainly determined by the driving force and drag force acting on the micromotors. Based on the hydromechanics theory, a hydrodynamic model is established to predict the drag force for a conical micromotor immersed in the flow field. By using the computational fluid dynamics software Fluent 18.0 (ANSYS), the drag force and the drag coefficient of different conical micromotors are calculated. A mathematical model was proposed to describe the relationship among Reynolds numbers Re, the ratio λ, the semi-cone angle δ and the drag coefficient C(d) of the micromotors. This work provides theoretical support and reference for optimizing the design and development of conical micromotors.